Development of new cytogenetic markers for Thinopyrum ponticum (Podp.) Z.-W. Liu & R.-C. Wang - Kroupin, Pavel Yu. (Comp Cytogenet, 2019)
Abstract. Thinopyrum ponticum (Podpěra, 1902) Z.-W. Liu & R.-C.Wang, 1993 is an important polyploid wild perennial Triticeae species that is widely used as a source of valuable genes for wheat but its genomic constitution has long been debated. For its chromosome identification, only a limited set of FISH probes has been used. The development of new cytogenetic markers for Th. ponticum chromosomes is of great importance both for cytogenetic characterization of wheat-wheatgrass hybrids and for fundamental comparative studies of phylogenetic relationships between species. Here, we report on the development of five cytogenetic markers for Th. ponticum based on repetitive satellite DNA of which sequences were selected from the whole genome sequence of Aegilops tauschii Cosson, 1849. Using real-time quantitative PCR we estimated the abundance of the found repeats: P720 and P427 had the highest abundance and P132, P332 and P170 had lower quantity in Th. ponticum genome. Using fluorescence in situ hybridization (FISH) we localized five repeats to different regions of the chromosomes of Th. ponticum. Using reprobing multicolor FISH we colocalized the probes between each other. The distribution of these found repeats in the Triticeae genomes and its usability as cytogenetic markers for chromosomes of Th. ponticum are discussed.